Jam, too? - Brown-Wood, JaNay; e (New York : Nancy Paulsen Books, 2024)
A jam session forms, instrument by instrument, and welcomes a child who loves dancing along.
Pub Weekly, February 2024
Kirkus Starred, December 2023
Booklist, February 2024
Bulletin (Center for Children's Books), January 2024
School Library Journal starred, May 2024
K-3
Keywords: Musical instruments -- Juvenile fiction; Dance -- Juvenile fiction; Musical instruments -- Fiction; Dance -- Fiction; Stories in rhyme; Beaches -- Juvenile fiction; Beaches -- Fiction